PENGENALAN AI DAN LITERASI DIGITAL UNTUK SISWA SMP MUHAMMADIYAH 32 GUNUNGSITOLI - Cut Tiur Mentari; Falentinus Teguh Karya Telaumbanua; Meiman Hidayat Waruwu; Palindungan Lahagu; Heniwati Gulo; Robin Markus Putra Waruwu (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This Community Service Program was conducted at SMP Swasta Muhammadiyah 32 Gunungsitoli with the aim of enhancing students' understanding of digital literacy and introducing artificial intelligence (AI) in daily life. Through interactive material delivery, discussions, and hands-on practice using AI-based applications, students were guided to grasp basic AI concepts, its benefits and risks, and its application in learning processes. The results showed that students were able to understand AI’s role in supporting education, distinguish between AI-generated and human-created images, and express curiosity about issues related to digital ethics and data security. A reflective approach was also employed by allowing students to ask questions and share critical perspectives. This activity demonstrated that an appropriate educational approach can foster responsible digital awareness from an early age, while also preparing young generations to face the challenges of the digital era.